2013
DOI: 10.1073/pnas.1313903110
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural architecture of the human dorsal frontoparietal attention network

Abstract: The dorsal frontoparietal attention network has been subdivided into at least eight areas in humans. However, the circuitry linking these areas and the functions of different circuit paths remain unclear. Using a combination of neuroimaging techniques to map spatial representations in frontoparietal areas, their functional interactions, and structural connections, we demonstrate different pathways across human dorsal frontoparietal cortex for the control of spatial attention. Our results are consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
125
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 51 publications
7
125
1
Order By: Relevance
“…This prioritization is widely believed to reflect the biasing of perceptual processing systems to favor material that will support current processing goals at the expense of material that will not; these biases have their source in a broadly distributed network of frontal and parietal regions (Desimone & Duncan, 1995). A dorsal attentional network that includes the frontal eye-fields (FEF) and the superior aspect of the intra-parietal sulcus (IPS) maintains attentional biases towards information that supports current task goals (Kincade et al, 2005;Szczepanski et al, 2010Szczepanski et al, , 2013Kastner et al, 2007). Successful attentional function, however, requires not only that biases towards task-relevant material be generally maintained across task conditions; but also they will interact with the specific context of the current stimulus environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prioritization is widely believed to reflect the biasing of perceptual processing systems to favor material that will support current processing goals at the expense of material that will not; these biases have their source in a broadly distributed network of frontal and parietal regions (Desimone & Duncan, 1995). A dorsal attentional network that includes the frontal eye-fields (FEF) and the superior aspect of the intra-parietal sulcus (IPS) maintains attentional biases towards information that supports current task goals (Kincade et al, 2005;Szczepanski et al, 2010Szczepanski et al, , 2013Kastner et al, 2007). Successful attentional function, however, requires not only that biases towards task-relevant material be generally maintained across task conditions; but also they will interact with the specific context of the current stimulus environment.…”
Section: Introductionmentioning
confidence: 99%
“…Attentional biases in favor of task-relevant information are generally thought to be instantiated and maintained by the dorsal attentional system (Kincade et al, 2005;Szczepanski et al, 2010Szczepanski et al, , 2013Kastner et al, 2007;Zhou & Desimone, 2011). Trial history effects have been found within the dorsal attentional systems of both human and non-human primates (Kristjansson et al, 2007;Bichot & Schall, 1999;2002); this system is generally more challenged (or less efficient) if the specific stimulus characteristics consistent with task goals vary from trial to trial.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, structural connectivity is defined using probabilistic tractography to determine the likelihood that two regions are joined by a direct white matter pathway. With regards to the IPS, posterior regions show preferential connectivity with dorsal and ventral visual regions (Bray et al, 2013b;Greenberg et al, 2012), while anterior regions show more probable connections to prefrontal and pre-motor regions (Bray et al, 2013b;Mars et al, 2011;Szczepanski et al, 2013). Lesion studies (Vandenberghe et al, 2012) and task activation and connectivity studies (Hutchinson et al, 2015) further support functional sub-divisions along the IPS.…”
Section: Introductionmentioning
confidence: 69%
“…These regions show differences in functional responses across tasks (Bray et al, 2013a;Sheremata et al, 2010;Silver and Kastner, 2009;Swisher et al, 2007;Szczepanski et al, 2013), and differential white matter structural connectivity to visual regions and parts of the dorsal attention network (Bray et al, 2013b;Greenberg et al, 2012;Szczepanski et al, 2013). In these studies, structural connectivity is defined using probabilistic tractography to determine the likelihood that two regions are joined by a direct white matter pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we find that as participants develop a more categorical representational space (as indicated by behavioral DSMs), a dorsal-to-ventral shift occurs in the neural informational networks representing those conceptual categories. This shift may be NEURAL REPRESENTATIONS OF ENGINEERING CONCEPTS 34 indicative of a transition in attention from the visuospatial configuration of features within a given image, processed by the dorsal stream (Haxby et al, 1991;Szczepanski, Pinsk, Douglas, Kastner, & Saalmann, 2013), toward a focus on higher-level categorization across the image set (Chi et al, 1981), which is associated with processing in the ventral stream (Kravitz et al, 2011;McGugin, Newton, Gore, & Gauthier, 2014;Tarr & Gauthier, 2000). Additionally, within the ventral stream, more anterior informational networks more strongly reflect the learned categorical structure for both groups of participants.…”
Section: Discussionmentioning
confidence: 97%